GC-MS Analysis of Essential Oils from Selected Aromatic Plants of the Manang Region, Nepal - Pradhan, Samjhana; Maharjan, Romi; Kandel, Dhan Raj (Journal of Plant Resources, 2025)
This study investigated the chemical composition of essential oils extracted from seven aromatic plant species collected from Manang district, Nepal; Artemisia dubia Wall. ex Besser, Elsholtzia fruticosa (D. Don) Rehder, Tetrataenium lallii (C.Norman) Cauwet, Carb & M.Farille, Juniperus indica Bertol., Nepeta ciliaris Benth., Origanum vulgare L., and Thymus linearis Benth. Essential oils were obtained through hydro distillation using the Clevenger apparatus and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The analysis revealed a diverse array of terpenoid compounds, predominantly monoterpenes, sesquiterpenes, phenols and esters, in the investigated plant species. Artemisia and Elsholtzia contained ã-terpinene and terpene derivatives as the main components. Chamazulene was also found in the Artemisia essential oil. Heracleum was characterized by esters (esters of acetic acid and butanoic acid) and D-limonene, while Juniperus contained D-limonene, sabinene, and elemol as major constituents. Nepeta was rich in bergamotene, caryophyllene oxide, and sesquisabinene. Origanum primarily consisted of p-cymene and thymol, and Thymus essential oil was highly rich in thymol and carvacol. This research contributes to expanding our understanding of the chemical diversity of essential oils from high-altitude aromatic plants in the Nepalese Himalayas, providing valuable information for potential applications in various industries. The identification of novel compounds and the understanding of their biological activities could lead to the development of new natural products with potential applications in pharmaceuticals, cosmetics, and food industries.